Annie Sullivan and the trials of Helen Keller - Lambert, Joseph, 1984- (Disney/Hyperion Books, 2018)
In graphic novel format, portrays the lives of Annie Sullivan and Helen Keller, how Annie went about teaching Helen to read, write, and talk through sign language.